iPhone Cool Projects - Bennett, Gary (Apress, 2012)
This book picks up where “Beginning iPhone Development” leaves off. The projects herein were developed specifically for this book, but these are no lightweight applications. Some projects are based on shipping products, showing how various technologies are integrated into a cohesive application. Other projects cover difficult topics and thus are more focused. The projects illustrate advanced topics such as game timers, XML parsing, streaming audio, multithreading, recognizing advanced gestures, and even designing your own network protocol using UDP (and why you would want to do this). You’ll be discussing mutexes, race conditions, sockets, packets, and endianness in no time! Those who want to develop immersive games have long heard that using a game engine is important, but getting started has been a challenge. Here at last is a game that is built around the open source cocos2d game engine, explained in great detail.